Developing EFL Students’ Listening Comprehension Through The Use Of Authentic Materials - Kochkorova, Zulfizar (Indonesian Journal Publisher, 2025)
The acquisition of language skills requires listening skills as a base yet English as Foreign Language (EFL) students face difficulties in spoken discourse understanding mainly due to fast speech speeds and unfamiliar words and diverse accents. A research analysis evaluates how authentic listening resources composed of real-life content from news broadcasts and podcasts and recorded conversations effectively teach students to listen more effectively. The study implemented a quasi-experimental method to evaluate 60 intermediate EFL learners through experimental (authentic materials) and control (textbook-based listening exercises) groups. Students who listened to original materials achieved much better results in listening comprehension than the control group students according to assessment results. The use of authentic materials boosted educational engagement and student motivation so they developed improved listening skills together with ability to process real-world language. Structural scaffolding options helped students manage problems related to fast speech rates and cultural references when processing the materials.